Cardiovascular risk factors in patients before and after antiretrovirals initiation in Sub-Saharan Africa, Temprano trial ANRS 12136 experience - (:unkn) unknown (My University, 2016)
The international initiatives for promoting access to antiretroviral therapy (ART) have reduced HIV- related morbidity and mortality. Meanwhile, there are growing cardiovascular risk factors (CVRF) in developing countries, which are witnessing an epidemiological transition. Our objective was to assess the significance of CVRF before and after initiating antiretroviral therapy in HIV-infected people in Africa. Temprano trial aimed to assess the benefits and risks of early antiretroviral therapy and 6-month isoniazid preventive therapy (IPT) after 30-month follow-up. This study concluded that both interventions are effective to reduce severe morbidity, what led WHO, in 2015, to recommend starting ART immediately if CD4 count drop below 500 cells / mm3. In this study, we assessed the prevalence of CVRF and the significance of obesity and overweight at baseline and after 24 months of ART in particular. We then assess the cardiovascular risk score according to the Framingham equation, with and without lipids, at baseline and at the end of follow-up. There were: (i) a positive correlation between the 2 equations (ii) a sharper increase in cardiovascular risks among women and (iii) no difference in the risk increase according to treatment strategies. Finally, in the long-term follow-up of Temprano trial, we are showing the efficacy of IPT on the reduction of mortality, which brings hope in a context where, despite the on-going epidemiological transition, the causes of deaths are still dominated by Tuberculosis in sub- Saharan Africa.
Keywords: African Research